2019
DOI: 10.1038/s41598-019-48149-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimating nutrient uptake requirements for radish in China based on QUEFTS model

Abstract: Imbalanced fertilization has caused lower yield and nutrient use efficiency for radish ( Raphanus sativus L.) production in China. Estimating nutrient requirements for radish is crucial in optimizing fertilization to resolve the problem. On-farm experiments in the radish-growing regions of China from 2000 to 2017 were collected to investigate the relationship between fleshy root yield and nutrient accumulation in radish plant using the Quantitative Evaluation of the Fertility of Tropical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In the present study, the data with HI lower 0.4 was removed due to the fact that the crop yields had been subjected to different constraints, such as disease, pests, and drought, with the exception of N, P, or K supply limitations [23]. The parameters of a and d were calculated using data with HI ranging from 0.4 to 0.82 in order to ensure that the peanut growth had been mainly limited by nutrient constraints rather than biotic or abiotic stress conditions.…”
Section: Selection Of the Data For Adapting The Quefts Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the data with HI lower 0.4 was removed due to the fact that the crop yields had been subjected to different constraints, such as disease, pests, and drought, with the exception of N, P, or K supply limitations [23]. The parameters of a and d were calculated using data with HI ranging from 0.4 to 0.82 in order to ensure that the peanut growth had been mainly limited by nutrient constraints rather than biotic or abiotic stress conditions.…”
Section: Selection Of the Data For Adapting The Quefts Modelmentioning
confidence: 99%
“…The QUEFTS model has been successfully applied to various crops in a range of different countries with a variety of soil types and agricultural environments. For instance, the model has been applied to such crops as maize [10,15], rice [16,17], wheat [18,19], soybean [20,21], sweet potato [22], and radish [23]. The QUEFTS model considers the interactions between the N, P, and K for a certain crop yield targets, and has been effectively used in combination with site-specific nutrient management (SSNM) methods in order to determine fertilizer requirements within site-specific areas [16,24].…”
Section: Introductionmentioning
confidence: 99%
“…The constant a and d of N, P, and K were 265 and 731, 1935 and 6044, and 199 and 595 kg/kg for all watermelons (Table 6), respectively. Other crops, such as radish, showed that the constant a and d of N, P, and K were 241 and 845, 1069 and 4480, and 171 and 879 kg/kg, respectively [58]. The constants of a and d represented the internal efficiency at maximum accumulation and maximum dilution of a nutrient.…”
Section: Selection Of Data For Adapting the Quefts Modelmentioning
confidence: 99%
“…Not only transfer of solutes, but also controlled-release fertilizers have also been objectives for simulation to have a clear understanding of the chemical and physiological processes (Shen et al 2015;Du et al 2004;Wang et al 1998). In addition, the nutrient uptake by plant roots has also simulated (Wu et al 2019;Zhang et al 2019;Louison et al 2015;Roose and Fowler 2004;Mankin and Fynn 1996). Historically, most simulations have focused on processes of individual nutrients occurring in soil, and little attention has been paid on mixed nutrients.…”
Section: Introductionmentioning
confidence: 99%